DEVELOPMENT OF SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS (STEM)-BASED E-BOOK ON HUMAN DIGESTIVE SYSTEM MATERIAL BASED ON SCIENTIFIC LITERACY - Sihombing, Rizky Agassy; Hasruddin, Hasruddin (Jurnal Pendidikan Matematika dan IPA, 2024)
Abstract The research was conducted on students"™ low scientific literacy skills in Indonesia based on PISA, PUSMENDIK data and the lack of science, technology, engineering, and mathematics (STEM)-based teaching materials that measure students"™ scientific literacy. Researcher develop teaching material in the form of interactive E-book that can be used on all devices with feasible based on scientific literacy skills on human digestive system material. The research method used is research and development (RD) with the analysis, design, development, implementation, and evaluation (ADDIE) from Branch. Subjects in this study was 4 experts (1 expert in media, learning design, material, and linguist). The instruments used are tests that experts and non-tests have validated. Test instruments assessment was given to 4 experts (1 expert in media, learning design, material, and linguist). The results showed that resulting validation from a media expert with xÌ„ = 98.3%, a material expert with xÌ„ = 83.3%, a learning design expert with xÌ„ = 95.3%, and a linguist expert with xÌ„ = 85%, and practically xÌ„ = 97, then an STEM-based E-book was declared feasible, and practically.